2021
DOI: 10.3233/bd-219007
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of NF-kB as a predictor of neoadjuvant chemotherapy response in breast cancer

Abstract: BACKGROUND: Cancer cells can defend themselves against apoptosis by activating NF-κB. Nuclear factor-kappa B (NF-κB) activity has also been associated with chemotherapy resistance. OBJECTIVE: We was aimed to investigate the relationship between NF-κB expression and intrinsic subtypes and anthracycline-based neoadjuvant chemotherapy responses in patients with locally advanced breast cancer. METHODS: This prospective cohort study examined NF-κB expression and intrinsic subtypes of breast cancer tissue using immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…However, nuclear NF-κB expression was recently found to be a predictive marker for the response to cyclophosphamide, doxorubicin, and fluorouracil chemotherapy regimens [ 21 ]. Additionally, Sampepajung et al [ 22 ] reported that patients with low nuclear NF-κB usually show a better response to chemotherapy than those with high levels of NF-κB. The function of cytoplasmic NF-κB has yet to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…However, nuclear NF-κB expression was recently found to be a predictive marker for the response to cyclophosphamide, doxorubicin, and fluorouracil chemotherapy regimens [ 21 ]. Additionally, Sampepajung et al [ 22 ] reported that patients with low nuclear NF-κB usually show a better response to chemotherapy than those with high levels of NF-κB. The function of cytoplasmic NF-κB has yet to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…The association between chemotherapy-induced NF-κB overactivation and drug resistance has been widely described [ 186 ]. As stated above, NF-κB inhibition could enhance the sensitivity of BC to chemotherapeutics and thus represents a potential strategy to overcome BC resistance [ 69 , 197 ]. Anti-cancer efficacy of flavonoids, including the effects on cancer chemoresistance, is a result of the capability of natural plant substances to affect each of the multistep processes of carcinogenesis via affecting numerous signaling pathways, such as NF-κB [ 198 , 199 ].…”
Section: Flavonoids As Suppressors Of Cancer Cell Plasticity and Cons...mentioning
confidence: 99%
“…Furthermore, NF-κB activity is frequently elevated in many tumor types, including leukemia, lymphoma, prostate cancer, breast cancer, colon cancer, melanoma, and head and neck cancer (Garg et al, 2003;Dolcet et al, 2005;Fan et al, 2013;Wu et al, 2017). NF-κB can be aberrantly activated in cancer by chemotherapeutic agents and ionizing radiation, response to stress, and induced cell death, leading to treatment-induced resistance of tumor cells (Jung and Dritschilo, 2001;Garg et al, 2003;Sampepajung et al, 2021). In vitro and in vivo studies have shown that NF-κB inhibits chemotherapy-induced apoptosis in various tumor types (Bharti and Aggarwal, 2002;Sampepajung et al, 2021).…”
Section: And Tumor Progression (Intercellular Adhesion Molecule 1 [Ic...mentioning
confidence: 99%
“…NF-κB can be aberrantly activated in cancer by chemotherapeutic agents and ionizing radiation, response to stress, and induced cell death, leading to treatment-induced resistance of tumor cells (Jung and Dritschilo, 2001;Garg et al, 2003;Sampepajung et al, 2021). In vitro and in vivo studies have shown that NF-κB inhibits chemotherapy-induced apoptosis in various tumor types (Bharti and Aggarwal, 2002;Sampepajung et al, 2021). For example, the upregulation of NF-κB-inducible genes has been shown to protect MDA MB-231 breast cancer cells from apoptosis induced by paclitaxel and ionizing radiation (Newton et al, 1999).…”
Section: And Tumor Progression (Intercellular Adhesion Molecule 1 [Ic...mentioning
confidence: 99%